Media Improvement for Detection Freezing Stressed Escherichia coli - Allawi, Saeed S; Ahmaed, Asmaa S; Yaseen, Ali A (Al-Nahrain Journal of Science, 2012)
Escherichia coli was injured by freezing at-18ºC. Surviving cells were recovered on nonselective medium (tryptone glucose extract agar) and selective medium (violet red bile salt agar) supplemented with compounds that degrade hydrogen peroxide or block its formation. Various concentrations of the following compounds were tested: sodium pyruvate, sodium thioglycolate,and n-propyl gallate.Sodium pyruvate and sodium thioglycolate, when added to either medium, significantly increased (P≤0.05) for recovering of injured cells. Supplementation of violet red bile agar increased recovery cells, but the counts remained considerably lower than the tryptone glucose extract agar counts. The repair detection of freezing stressed E.coli was greatly improved by the addition of sodium pyruvate and thioglycolate .We therefore recommend that pyruvate (0.4%) and thioglycolate (0.04%) be used to supplemented media in the repair detection procedure